Association between inhaled corticosteroid use and risk of hyperglycemia in patients with chronic obstructive pulmonary disease: A systematic review and meta-analysis - Fathur Nur Kholis; Kevin Gracia Pratama; Jessica Novia Hadiyanto (Tzu Chi Medical Journal)
Objectives: Chronic obstructive pulmonary disease (COPD) patients have a higher risk of developing diabetes, and studies suggest that inhaled corticosteroids (ICSs) use may be associated with a higher risk of diabetes, particularly at higher doses. This study aims to investigate the effects of ICS use on the risk of diabetes and blood glucose levels in COPD patients. Materials and Methods: A systematic search was carried out on the PubMed, EBSCOhost, and ProQuest databases using the terms “Inhaled Corticosteroids,” “Diabetes,” and “Chronic Obstructive Pulmonary Disease” for the period between 2013 and 2023. The systematic review adhered to the PRISMA 2020 guideline. A meta-analysis was conducted using a random-effects model using the RevMan 5 software. Results: A total of 14 studies were included in the final analysis, with 10 randomized controlled trials (RCTs) and 4 observational studies. Two observational studies investigated the relationship between ICS dose and diabetes risk. A meta-analysis of the RCTs studies showed a nonstatistically significant tendency toward increased blood glucose (odds ratio [OR] 1.07 and 95% confidence interval [CI] 0.88–1.30) after a 52-week follow-up. Whereas the observational studies showed a tendency toward an increased risk of diabetes (OR 1.40 and 95% CI 0.96–2.03). Furthermore, a subgroup meta-analysis of high-dose ICS (>900 μg/day) showed a significant increase in the risk of diabetes (OR 1.20 and 95% CI 1.09–1.32). Conclusion: Short-term use of ICS does not have a significant effect on blood glucose. However, long-term use, especially at higher doses, can increase the risk of developing diabetes.